The impact of active employment policy measures on the labor integration of persons with disabilities : https://doi.org/10.5937/etp2501126P - Počuč, Pavle (Ekonomija - teorija i praksa, 2025)
Sensitive and vulnerable groups in society must be provided with equal employment and social status with great empathy and social responsibility, as they are characterized by a strong desire to contribute to the community in which they live. In addition to the economic benefits that enable financial independence, persons with disabilities who are employed regain a sense of personal value, dignity, and equal status in society. The fact that they contribute to societal development through their work further motivates them and strengthens their sense of belonging to that society. Most persons with disabilities are marked by exceptional dedication, responsibility, discipline, and motivation; however, unfortunately, they are often unjustly neglected and discriminated against by employers. Through synchronized action and engagement of all three sectors, it is possible to significantly improve the position of persons with disabilities in the labor market and directly influence the strengthening of the country’s socio-economic status. By creating a clear strategy of assistance and support for employment led by the state, especially through concrete active employment policy measures, a noticeable trend in reducing their unemployment rates can be observed. The aim of this paper is to present the employment measures for hard-to-employ categories, with an emphasis on persons with disabilities, as well as to analyze the impact of these measures on the employment status and socio-economic position of persons with disabilities. Furthermore, the paper will present survey results along with future directions and recommendations.